The Influence of Thin Capitalization and The Executives Characteristics Toward Tax Avoidance by Manufacturers Registered on ISE in 2011-2015 - Dewi Prastiwi; Renni Ratnasari (AKRUAL: JURNAL AKUNTANSI, 2019)
This study aims to analyze the effect of thin capitalization and executives characteristics based on tax avoidance. The sample consists of 38 manufacturing companies listed on the Indonesia Stock Exchange in 2011-2015 and they will be determined by several criteria. The results of multiple regression analysis shows that the thin capitalization and executives characteristics positively affect tax avoidance. These results are consistent with the view that companies tend to increase interest of their debt (thin capitalization) to minimize the tax burden and the executives characteristics has an important role in the action.